Resistive Switching Prospects Of Aloe Vera-Based Thin Films For Nonvolatile Memory Application - Lim, Zhe Xi (2020)
Resistive switching represents a paradigm shift for nonvolatile memories. The phenomenon has been demonstrated using metal-insulator-metal (MIM) structures based on bio-organic materials. Aloe vera is a bio-organic insulator with potentials for various electronic applications. However, resistive switching has not been exhibited on Aloe vera-based devices. Therefore, the objective of this research is to investigate resistive switching using a MIM structure with Aloe vera gel as the insulator. The device exhibits bipolar resistive switching only if the gel is dried at 50°C. The gel needs to be dried together with 20–60 wt% of ethanol to enable resistive switching at other temperatures. The switching is attributed to space-charge-limited conduction. The top electrode has an impact on the switching mechanism, as the switching can also attributed to filamentary conduction if Ag or Al is used as the top electrode. The device demonstrates good performance, with wide read memory window (~5 V), large ON/OFF ratio (>105), long endurance cycle (>100 cycles), and excellent retention interval (≥104). Acemannan and pectin are responsible for the switching. The MIM structure based on the extracted polysaccharides exhibits both bipolar and unipolar switching depending on the choice of top electrode. The switching can be elucidated to various electronic, electrochemical, and thermochemical processes. The device delivers excellent performance, including a read memory window as wide as 5.2 V and an ON/OFF ratio as large as ~107. Moreover, the device OFF-state resistance can be modulated over 5 orders of magnitude by varying ICC and v. Conductance quantization with stepwise current increase at integer and half-integer multiples of quantum conductance can be achieved during the switching for multilevel data storage.